Big surgeons don’t need big incisions: Minimally invasive surgery and use of robotics in Otolaryngology: A Narrative Review - Huzaifa Moiz Hussain; Shabbir Akhtar (Journal of the Pakistan Medical Association, 2024)
Minimally invasive surgery (MIS) and robotics have revolutionized the field of Otolaryngology. MIS and robotics have reshaped traditional otolaryngological practices, offering patients a multitude of benefits. Reduced incision sizes and tissue manipulation minimize postoperative pain and discomfort, while also improving cosmetic outcomes. MIS has facilitated enhanced visualization and access to intricate anatomical structures, enabling the treatment of previously inaccessible lesions. MIS procedures also offer shorter hospital stays, reduced blood loss, and faster healing times whilst enhancing patient satisfaction and overall quality of life The ongoing progress in minimally invasive approaches solidifies their role as a cornerstone in modern Otolaryngology, and surgeons navigating this transformative landscape must embrace the learning curve associated with these advanced techniques, recognizing the potential for improved patient outcomes. This article explores the transformative impact of MIS and robotics on the diverse branches of Otolaryngology, highlighting the technological advancements that have enabled these techniques to flourish. Continue...